Analisis Kesalahan Numerasi Siswa Kelas 3 MI dalam Penulisan Lambang Bilangan Ribuan - Putri, Andri Nur Kusuma; Firdousiah, Lia Farah Camelia; Damayanti, Nia Wahyu (FKIP Universitas Wisnuwardhana, 2021)
The concept of recognizing number symbols is very important to understand because it is a basic concept in mathematics. Mathematical concepts that need to be introduced to early childhood are the concepts of numbers, calculation patterns, measurements, geometry, strategies in problem solving games. Numeral serves to concretize the concept of numbers that are still abstract. This research is a type of qualitative research with research subjects as many as 5 third grade students. In elementary school,, there are students who cannot pronounce and write number symbols correctly. This may be an indicator of a student having difficulty in numeracy.